RE-USE INTENTION IN USING M-WALLET TOWARD PERCEIVED OF RISK, PERCEIVED EASE OF USE, USEFULNESS, BENEFIT AND SATISFACTION IN OVO ELECTRONIC PAYMENT (A CASE STUDY ON FACULTY OF ECONOMICS AND BUSINESS AT UNIVERSITAS BRAWIJAYA) - Alexander Jascha P. Napitupulu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims to examine the influence of perceived of risk, ease of use, usefulness, and benefit on customers who use electronic/mobile wallet system and examine the influence of satisfaction toward the re-using intention of M-Wallet. This is a quantitative research that investigated the relationship between constructs. These constructs are the effect of perceived of risk, perceived ease of use, usefulness, benefit, and satisfaction toward to re-use intention of M- Wallet. The sample in this study used the Slovin formula with 293 active respondents from undergraduate students from the Accounting Department of the Faculty of Economics and Business, Universitas Brawijaya. The statistical method used to test the hypothesis proposed in this study is Partial Least Square (PLS) with the help of the Smart PLS version 3. The results of this study indicate that the perceived of risk, perceived ease of use, perceived of usefulness, and perceived benefits has a positive influence on perceived satisfaction. It is expected that the company can maintain and improve service to the Perceived of Ease of Use, by increasing convenience for consumers so that the Perceived of Satisfaction will increase and influence the intention to Re-Using OVO. Moreover, perceived satisfaction (Y) affects individuals to be interested in reusing electronic payments using OVO (Z). Thus, it can be concluded that the higher the perception of satisfaction, the higher the effect on the re-using electronic payments intention in OVO. Keywords : Perceived of Risk, Perceived of Ease of Use, Perceived of Usefulness, Perceived of Benefit, Perceived of Satisfaction, Re-Using Intention